2007
DOI: 10.1074/jbc.m610350200
|View full text |Cite
|
Sign up to set email alerts
|

Survivin Down-regulation Plays a Crucial Role in 3-Hydroxy-3-methylglutaryl Coenzyme A Reductase Inhibitor-induced Apoptosis in Cancer

Abstract: 3-Hydroxy-3-methylglutaryl coenzyme A reductase inhibitors (HRIs) are widely used to reduce serum cholesterol in patients with hypercholesterolemia. Previous studies have shown that HRIs can induce apoptosis in colon cancer cells. In this study, we investigated the mechanisms underlying the apoptosis-inducing effect of HRIs in greater detail. The HRI lovastatin induced apoptosis in the human colon cancer cell line SW480 by blocking the cholesterol synthesis pathway. Immunoblot analysis of antiapoptotic molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
53
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 51 publications
8
53
1
Order By: Relevance
“…YM155 alone and the combination of YM155 and simvastatin also inhibited tumor growth by Caki-1-staR cells through the down-regulation of survivin in vivo. Kaneko et al reported that the down-regulation of survivin by RNA interference induced apoptosis in a human colon cancer cell line, while its overexpression rendered cells resistant to lovastatin-induced growth inhibition (35). Our results are consistent with these findings.…”
Section: Discussionsupporting
confidence: 92%
“…YM155 alone and the combination of YM155 and simvastatin also inhibited tumor growth by Caki-1-staR cells through the down-regulation of survivin in vivo. Kaneko et al reported that the down-regulation of survivin by RNA interference induced apoptosis in a human colon cancer cell line, while its overexpression rendered cells resistant to lovastatin-induced growth inhibition (35). Our results are consistent with these findings.…”
Section: Discussionsupporting
confidence: 92%
“…Shepherdin interferes with hsp90 chaperone activity thereby repressing expression of its target protein, survivin, and induces cell death in transformed cells but not in normal cells (34). We and others have shown that inhibition of the Ras and Akt pathway suppresses survivin expression (35)(36)(37). p73 activation found in this study, is a novel mechanism for targeting survivin in cancer cells.…”
Section: Discussionsupporting
confidence: 50%
“…We have hypothesized several potential mechanisms for apoptosis: accumulation of toxic lipid metabolites 24 and reduction of survival factors. 25 However, we failed to obtain evidence for the involvement of ceramide and survivin in apoptosis.…”
Section: Liver-specific Knockout Mice Of Hmg-coa Reductase 1829mentioning
confidence: 82%